Design of a Compact Narrowband Microstrip Patch Antenna using Multilateral Slots for Radar Applications (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Abstract: The fascinating features of microstrip patch antenna such as lightweight, low cost, and low-profile planar configuration, which account for easy fabrication, led to its gaining popularity in the recent past. However, designers are struggling to overcome its major demerits such as low gain, low directivity, and low efficiency. The most common option for parameter improvement was the use of parasitic patches, increased substrate height, or implementation of the antenna array, all of which results in cumbersome design. This article presents a single element narrowband microstrip patch antenna, for radar applications. The radiating patch of the antenna was mounted on Flame Retardant Circuit Board (FR-4), and fed with 50â„¦ microstrip feedline, using the edge-feeding technique. Multilateral slots were cut on the patch for better impedance matching and gain enhancement. The total dimension of the patch was 15.8x11.5mm2. Simulation results using Finite Element Method show that the proposed antenna operates at a resonant frequency of 8.5GHz, with a bandwidth of 200MHz. The antenna exhibits a good reflection coefficient of -40.35dB, a very low VSWR of 1.02. and a maximum gain of 6.4dB at the same resonant frequency. The efficiency of the antenna was also improved to 99%. Comparison of the proposed antenna with previously reported literature indicated that the proposed antenna is the best candidate for specific Radar applications
Keywords: Multilateral slot; Narrowband; FR-4 Substrate; Micro-strip; VSWR; Radar application